Potential Histopathological and Immune Biomarkers in Malignant and Non-Malignant Oral Lesions - Vinícius Gonçalves de Souza; Aparecida de Lourdes Carvalho; Carla Silva Siqueira Miranda; Ludimila Paula Vaz Cardoso (Stilus Optimus, 2022)
Objectives: The presented case-control study was developed to characterize the clinical, histopathological and immunological profile of patients with traumatic injuries, benign neoplasms, potentially malignant oral disorders and malignant neoplasms of the oral cavity, in order to identify biomarkers of malignancy. Material and Methods: Clinical information was collected from dental records and several techniques were performed, including histopathological evaluation in sections stained with haematoxylin and eosin, immunohistochemistry for programmed death ligand-1 and measurement of serum levels of interferon-gamma, interleukin-6, -10 and -12. Statistical analysis was performed using IBM SPSS® Statistics software. Results: This study included 8 patients with traumatic injuries, 8 with benign neoplasms, 6 with potentially malignant oral disorders and 11 with malignant neoplasms. An association was observed between the classification of the lesion and smoking (P < 0.05), the size of the lesion (P < 0.05), the density of the inflammatory infiltrate (P < 0.001), the degree of dysplasia (P < 0.01) and programmed death ligand-1 expression (P < 0.01). Conclusions: Therefore, it is suggested that smoking, the size of the lesion, the inflammatory infiltrate and the programmed death ligand-1 expression can be considered potential biomarkers of oral malignancy.